Social Choice, Social Sustainability, and Why the Neoclassical Approach Fails to See the Difference - Okhrimenko, Iana (Journal of Public Governance, 2020)
Objectives: The neoclassical economic framework is a dominant approach in both theoretical and applied fields, such as public policy design. Despite the substantial amount of criticism towards the neoclassical assumptions of rational choice and obstacles related to preference aggregation, there is a minor concern regarding the underlying philosophy of the mainstream public policy design, namely static social utility maximisation under exogenously given social preferences.This paper analyses the inherent biases of the public policy based on the neoclassical background, attempting to prove that although such an approach can theoretically lead to the socially optimal outcome, it is hardly in line with the long-run social survival and development objectives. Other than this, the paper attempts to explore how incorporating alternative approaches towards individual and collective rationality into the theory of social choice can allow for designing a more sustainable public policy.Research Design & Methods: The paper presents the review of the relevant literature alongside the theoretical inquiry into the underlying logic and philosophy of the neoclassical approach towards the public policy design as well as the most relevant non-mainstream theories.Findings: It is demonstrated that the assumptions behind the neoclassical framework are inconsistent with the notions of social evolution and social sustainability.Implications / Recommendation: The persistent idea that public policymakers should attempt to maximise social utility implies artificial limitations for public policy as well as ill-designed goals and objectives. There is a strong need to reconsider the appropriateness of using the neoclassical analytical framework in public policy design.Contribution / Value added: The framework discussed in this article serves as the ground for more sustainable public policy design principles.